Periosteum: A Highly Underrated Tool in Dentistry - Ajay Mahajan (Hindawi Limited, 2012)
The ultimate goal of any dental treatment is the regeneration of lost tissues and alveolar bone. Under the appropriate culture conditions, periosteal cells secrete extracellular matrix and form a membranous structure. The periosteum can be easily harvested from the patient's own oral cavity, where the resulting donor site wound is invisible. Owing to the above reasons, the periosteum offers a rich cell source for bone tissue engineering; hence, the regenerative potential of periosteum is immense. Although the use of periosteum as a regenerative tool has been extensive in general medical field, the regenerative potential of periosteum is highly underestimated in dentistry; therefore, the present paper reviews the current literature related to the regenerative potential of periosteum and gives an insight to the future use of periosteum in dentistry.